Wild bee diversity is enhanced by experimental removal of timber harvest residue within intensively managed conifer forest. Issue 10 (1st August 2018) - Rivers, James W.; Mathis, Codey L.; Moldenke, Andrew R.; Betts, Matthew G.
Abstract: The use of timber harvest residue as an energy source is thought to have environmental benefits relative to food‐based crops, yet the ecological impact of this practice remains largely unknown. We assessed whether the abundance and diversity of wild bees (Apoidea) were influenced by the removal of harvest residue and associated soil compaction within managed conifer forest in western Oregon, USA. We sampled bees over two years (2014–2015) on study plots that were subjected to five treatments representing gradients in removal of harvest residue and soil compaction. We collected >7, 500 bee specimens from 92 distinct species/morphospecies that represented five of the seven bee families. We trapped 3x more individuals in the second year of the study despite identical sampling effort in both years, with most trapped bees classified as ground‐nesting species. Members of the sweat bee family (Halictidae) comprised more than half of all specimens, and the most abundant genus was composed of metallic green bees ( Agapostemon, 33.6%), followed by long‐horned bees ( Melissodes, 16.5%), sweat bees ( Halictus, 15.9%), and bumble bees ( Bombus, 13.6%). In both years, abundance and observed species richness were greatest in the most intensive harvest residue treatment, with other treatments having similar values for both measures. Our study indicates that early successional managed conifer forest that has experienced removal of harvest residue can harbor a surprising diversity of wild bees, which are likely to have important contributions to the broader ecological community through the pollination services they provide. Abstract : Despite interest in forest harvest residues as an alternative to fossil fuels, little is known about how removing these components from forests influences native pollinators. The results from this study found that the removal of forest harvest residues and associated organic materials was linked to increased bee diversity, likely because it provided new nesting habitat that was suitable for ground‐nesting bee species.